(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
One of the main causes of early failure of paving is water flow within its surface layers. In this study, a new experimental work has been proposed to increase the permeability coefficient using two specifications aggregates (G1 and G2) and to increase the coarse gradient ratios subjected to the scrb2003 limits. This enables the angularity of aggregates to maintain coherence and to ensure acceptable stability characteristics. In order to accomplish this purpose, several models have been prepared to study the effect of increasing proportions of coarse aggregate on the properties and whether they serve the desired purpose. The results showed an increase in the stability of G2 in general in contrast with the results of G1. The permeability coefficient also increased for G2 mixtures by 0.005. Indirect tensile testing demonstrated an increase in T.S.R of 10.5% for the specification of G2.